Class with negative coefficients and convex with respect to symmetric points - Aini Janteng; Suzeini Abdul Halim (Hikari Ltd, 2010)
Let C_s T(A,B) denote the class of functions f(z)=z-∑_(n=2)^∞ a_n z^n which are analytic in an open unit disc D={z:|z|<1} and satisfying the condition (2(zf^' (z))^')/((f(z)-f(-z))^' )≺(1+Az)/(1+Bz),-1≤B<A≤1,z∈D. The aims of paper are to determine coefficient estimates and distortion bounds for the class C_s T(A,B).